AGRESIVITAS PAJAK DITINJAU DARI PROFITABILITY, CAPITAL INTENSITY, DAN INVENTORY INTENSITY - Fatikah Gustie Aisyah (JURNAL ILMIAH EDUNOMIKA, 2026)
This study focuses on investigating how profitability, capital intensity, and inventory capacity impact tax aggressiveness. The study subjects included all issuers listed on the Indonesia Stock Exchange for the 2019-2023 period. A quantitative approach was applied in this study, utilizing secondary data sourced from issuers' financial statements and annual reports. Data analysis was performed using multiple linear regression analysis. The study's findings indicate a positive correlation between capital intensity and corporate tax aggressiveness. Furthermore, profitability and inventory capacity were shown to have no significant influence in this model.  Keywords: Profitability, Capital Intensity, Inventory Intensity, Tax Aggressiveness   Keywords: Profitability, Capital Intensity, Inventory Intensity, Tax Aggressiveness